Effects of academic self-regulation on procrastination, academic stress and anxiety, resilience and academic performance in a sample of Spanish secondary school students - Ragusa, Antonio; González-Bernal, Jeronimo; Trigueros, Ruben; Caggiano, Valeria; Navarro, Noelia; Minguez-Minguez, Luis A.; Obregón, Ana I.; Fernandez-Ortega, Carmen (Frontiers in Psychology, 2023)
INTRODUCTION: One of the biggest challenges facing students today is procrastination, which is closely related to stress, anxiety and, in the most severe cases, depression. The aim of the present study is to analyse the influence of academic self-regulation on procrastination, academic anxiety and stress, academic resilience and academic performance. METHOD: The sample consisted of 991 high school students aged between 16 and 19 years (M = 17.25; SD=3.45). A structural equation model was used to analyse the relationship between the study variables. RESULTS: Analyses showed that academic self-regulation negatively predicted procrastination. In turn, procrastination positively predicted academic stress and anxiety. However, resilience exerted a protective influence by being positively related to academic stress and anxiety. Finally, resilience positively predicted academic performance, whereas stress and anxiety negatively predicted academic performance. CONCLUSION: Thus, the importance of generating strategies for students to learn to self-regulate in academic contexts, manage emotions, foster motivation and develop strategies to help them overcome the vicissitudes they face is emphasised.